The Diversity of Potential Malaria and Dengue Mosquito Vector from Bangsring Village Wongsorejo District Banyuwangi East Java - Azkiyah, Siti Fat'hiyatul; Senjarini, Kartika; Oktarianti, Rike; Wiyono, Hidayat Teguh; Wathon, Syubanul (Jurnal ILMU DASAR, 2021)
Bangsring village in Wongsorejo regency has been reported as malaria endemic area in Banyuwangi since 2011. Understanding the diversity and behavior of mosquito vector in this area will be very impotant in developing vector control program. The masquitoes were collected by landing collection outside and inside house by human bites, we also observed the area around cattle cage. During observation periods, a total 633 masquitos were collected consist of 44% malaria potential vector (Anopheles spp.) 19% Dengue fever (DF) potential vector (Aedes spp.) and 36% were not belong to both of them. Out of total collected Anopheles spp. mosquitoes about 65% were indentified as An. vagus, 25% were An. indevinitus, 8% were An. vagus (limosus), and only 2% as well as 0,04 % were An. supictus and An. kochi. Meanwhile we found 19% of Aedes sp. were Ae. aegypti and 81% were Ae. albopictus. This study showed that the dominan potential malaria’s vector is An. Vagus and the dominan DF vector is Ae. albopictus. Mostly colleted Anopheles sp. were exophagic and zoophilic with the highest activities between 06.00-08.00 pm. This was in contras to Aedes sp. where mosfly found endophilic and it has 2 hightime of activities Aedes sp. between 06.00- 07.00 AM and 05.00-06.00 PM. Keywords: Dengue, Malaria, diversity, Anopheles, Aedes.